PENGARUH PENGGUNAAN MEDIA SOSIAL FACEBOOK TERHADAP PERILAKU PROSOSIAL REMAJA DI KENAGARIAN KOTO BANGUN - Fela Asmaya; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
the technology advances, the number of social media users is also increasing every year. As a result, positive and negative impacts caused social media is also an impact on the user. One of the effects of the use of social media is an influence on prosocial behavior that occurs among teenagers by using information technology, especially the use of social media facebook. The purpose of this study was to determine how much influence the use of social media facebook toward prosocial behavior of teenagers in Kenagarian Koto Bangun.This study uses quantitative methods. Data collection techniques in this study using a questionnaire. The total sample for this study as many as 85 respondents and using random sampling techniques. To determine the influence of these two variables, the researchers used a simple linear regression analysis. As for the processing of the questionnaire test, carried out using statistics program Product And Service Solution (SPSS) Windows version 20.These results indicate that the effect of the use of social media facebook toward prosocial behavior of teenagers in Kenagarian Koto Bangun regression coefficients obtained results in this study is Y = 14,349+ 0,206 X with a level of significance of 0.001 is smaller than α = 0.05. Thus, Ha received Ho is rejected, meaning that there is a considerable influence between the variables of social media use facebook to variable prosocial behavior with a contribution of 62.6% strong category.The percentage of shows including the strong influence between the use of social media facebook toward prosocial behavior of teenagers in Kenagarian Koto Bangun.